Dynamic Analyses of Drosophila Gastrulation Provide Insights into Collective Cell Migration - McMahon, Amy (2008)
The concerted movement of cells from different germ layers contributes to morphogenesis during early embryonic development. Using an optimized imaging approach and quantitative methods, we analyzed the trajectories of hundreds of ectodermal cells and internalized mesodermal cells within Drosophila embryos over 2 hours during gastrulation. We found a high level of cellular organization, with mesoderm cell movements correlating with some but not all ectoderm movements. During migration, the mesoderm population underwent two ordered waves of cell division and synchronous cell intercalation, and cells at the leading edge stably maintained position. Fibroblast growth factor (FGF) signaling guides mesodermal cell migration; however, we found some directed dorsal migration in an FGF receptor mutant, which suggests that additional signals are involved. Thus, decomposing complex cellular movements can provide detailed insights into collective cell migration.